2012
DOI: 10.1016/j.enbuild.2011.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Home energy consumption feedback: A user survey

Abstract: Buildings account for a relevant fraction of the energy consumed by a country, up to 20-40% of the yearly energy consumption. If only electricity is considered, the fraction is even bigger, reaching around 73% of the total electricity consumption, equally divided into residential and commercial dwellings. Building and Home Automation have a potential to profoundly impact current and future buildings' energy efficiency by informing users about their current consumption patterns, by suggesting more efficient beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(42 citation statements)
references
References 15 publications
2
39
0
1
Order By: Relevance
“…Results showed that users preferred environmentally-friendly units (here, the equivalent number of trees required to offset CO2 emissions associated with their electricity consumption) to kilowatt-hours (kWh). This is consistent with previous studies [14,15] showing that people have a limited understanding of kWh due to its abstract nature (hard to visualize).…”
Section: Resultssupporting
confidence: 82%
“…Results showed that users preferred environmentally-friendly units (here, the equivalent number of trees required to offset CO2 emissions associated with their electricity consumption) to kilowatt-hours (kWh). This is consistent with previous studies [14,15] showing that people have a limited understanding of kWh due to its abstract nature (hard to visualize).…”
Section: Resultssupporting
confidence: 82%
“…Ignoring this step might lead to getting worse energy-consumption behaviors. In [162][163][164], the results indicate that the occupants had a limited understanding of the goal of the feedback studies and that some occupants had a hard time understanding the used representative units. In such cases, a pre-survey could help identify the general knowledge of the targeted occupants for the feedback study and could help reveal which representative units would work better for them.…”
Section: Improving Occupant Energy-consuming Behaviorsmentioning
confidence: 88%
“…Although the efficiency of this method has shown to be lower [38,41], it can enhance the user's motivation to reduce their electricity consumption by up to 5% [42]. It is possible to send signals to the end-users to warn them about overconsumption; the current concept is a fix daily limit when a warning is sent once the consumption goes above the defined limit [43]. This means that warnings would always occur towards the end of the day, whilst the limit should be changing and adapting to real time variation, to make use of potential savings made throughout the day.…”
Section: Target-based Feedbacksmentioning
confidence: 99%